Heat stress during American football - Adams, W. M.; Belval, L. N.; Hosokawa, Y.; Grundstein, A. J.; Casaages, D. J. (Heat stress in sport and exercise. Thermophysiology of health and performance, 2019)
American football is a team sport involving cycles of short duration, high-intensity bouts of exercise followed by a brief period of recovery. With the competitive season starting in August in the Northern hemisphere, athletes are subjected to potential extreme environmental conditions, which may have detrimental effects on athlete safety and performance. The purpose of this chapter is to discuss the physical characteristics of American football followed by the various strategies that can be utilized to maximize performance and enhance safety during exercise in hot environmental conditions.